2011
DOI: 10.1634/theoncologist.2011-0048
|View full text |Cite
|
Sign up to set email alerts
|

Breast Medical Oncologists' Use of Standard Prognostic Factors to Predict a 21-Gene Recurrence Score

Abstract: Background. Half of all breast cancers are early stage, lymph node negative, and hormone receptor positive. A 21-gene (Oncotype DX; Genomic Health, Inc., Redwood City, CA) recurrence score (RS) is prognostic for recurrence and predictive of chemotherapy benefit. We explored the ability of oncologists to predict the RS using standard prognostic criteria.Methods. Standard demographic and tumor prognostic criteria were obtained from patients with an available RS. Two academic pathologists provided tumor grade, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…These findings are consistent with those reported in other retrospective and prospective studies conducted in different regions of the world (European countries, Japan, Australia and the United States), [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and highlight the consistency of the impact of knowing the Recurrence Score result on adjuvant treatment decisions between regions and countries, despite variability in health care systems and treatment practices.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with those reported in other retrospective and prospective studies conducted in different regions of the world (European countries, Japan, Australia and the United States), [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and highlight the consistency of the impact of knowing the Recurrence Score result on adjuvant treatment decisions between regions and countries, despite variability in health care systems and treatment practices.…”
Section: Discussionsupporting
confidence: 89%
“…Of the 47 patients in our cohort, 25 (53.2%), 19 (40.4%) and 3 (6.4%) had a low (<18), intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) …”
Section: Recurrence Score and Risk Assessment By The St Gallen Criteriamentioning
confidence: 85%
See 1 more Smart Citation
“…A study exploring the ability of oncologists to predict the RS using standard prognostic criteria revealed that oncologists are able to differentiate between a low or intermediate RS and a high RS using standard prognostic criteria [12]. However, in this study, provision of the actual RS changed the treatment recommendations in nearly 20% of cases, most often in intermediate-risk cases, suggesting that the RS may reduce chemotherapy use [12].…”
Section: Discussionmentioning
confidence: 82%
“…However, in this study, provision of the actual RS changed the treatment recommendations in nearly 20% of cases, most often in intermediate-risk cases, suggesting that the RS may reduce chemotherapy use [12]. Another study looking at the ability of oncologists to estimate recurrence risk also showed that specialists tend to overestimate the risk of recurrence compared with RS, resulting in potential significant overtreatment of breast cancer patients with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 94%